LIMBAH CAIR TAHU DAN CUCIAN BERAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Miil.) - Indrawati Gelamona; Sofyan Samad; Shubzan A.M.; Hayun Abdullah; Sugeng Haryanto (AGROVITAL : Jurnal Ilmu Pertanian, 2022)
Tomato is a vegetable plant of the Solanaceae family that can grow in the middle plains and is about 3-4 months old. Biological, chemical and physical activities of soil with organic fertilizers. POC tofu liquid waste and rice water are given to increase production yields while reducing soil damage due to chemical fertilizers. The purpose of this study was the difference in tomato yield using tofu liquid waste POC and rice washing waste gave the best results for fruit. This study was a Randomized Block Design (RAK) with 15 experimental units consisting of 5 treatments and 3 replications. Based on the analysis of POC variance of tofu waste and rice washing waste on plant height variables, the number of primary, secondary branches, weight had a significant and very significant effect on flower and fruit variables. The results of the M2 treatment of rice washing waste produced the best results for all observation variables, namely plant height 79 cm, 2 primary branches, 13 secondary branches, 20 flowers, 14 fruits and 67 g. Rice washing waste contains elements of N, P, K and Ca which are easily absorbed by tomato plants.